What Drives Muzakki to Pay Zakat at Baitul Mal? - Fathin Azzahra; M. Shabri Abd Majid (Shirkah: Journal of Economics and Business, 2020)
The present study empirically explores the factors influencing the decision of Muzakki (zakat payers) to pay zakat at an official institution, i.e. Baitul Mal Banda Aceh, Indonesia.Â The factors comprise faith, altruism, service quality, role of the zakat economy, and role of Ulama (Islamic scholars). To gather the data, 140 questionnaires were disseminated to the participants who were selected based on the purposive sampling technique. The data were further analyzed by employing a binary logistic regression. The results of this study revealed that faith, altruism, service quality, role of the zakat economy, and role of Ulama significantly and positively affected the decision of Muzakki to pay zakat at Baitul Mal. These findings imply that to attract Muzakki to pay zakat at a Baitul Mal, it not only needs to enhance relevant knowledge about the obligation to pay zakat and its benefits, but it also needs to improve the quality of services provided by the Baitul Mal. All in all, Ulama also has an important role in influencing Muzakki to pay zakat at the Baitul Mal institution.